PERLINDUNGAN HUKUM TERHADAP KORBAN KEJAHATAN PERDAGANGAN ORANG (STUDI TENTANG IMPLEMENTASI UNDANG-UNDANG NO. 21 TAHUN 2007) - Lathifah Hanim; Adityo Putro Prakoso (UNISSULA, 2015)
Human Trafficking especially against women and children is a crime whose perpetrators must be severely punished. Most victims of trafficking are women and children whose educational level is low and the weak economic situation, therefore victims should receive legal protection. The method used in this research is juridical sociological or socio legal research, the method or procedure used to solve research problems by examining secondary data such as ingredients laws or regulations applicable law followed by conducting research on the data primer on the field. The results showed, 1) factors that cause human trafficking are poverty, low education, Promiscuity, lack of information. 2) obstacles in the legal protection for trafficking victims even though the government has issued Law No. 21 of 2007 on the Eradication of Trafficking in Persons, but it is unfortunate that the law can not be enforced effectively, because there are some obstacles in the form factor of non-juridical include economic factors, poverty, education factors are low and social and cultural factors.